Pendampingan UMKM Dalam Pembuatan NIB Dan Pembembangan Strategi Bisnis yang Berkelanjutan di Kec. Purwadadi Kab. Subang - Harisandi, Prasetyo; Yahya, Adibah; Mulyanto, Heru; Asral (Dinamika: Jurnal Pengabdian Masyarakat, 2024)
Community service in Purwadadi District, Subang Regency, West Java, in September-October 2024, aims to empower 30 start-up MSMEs in facing the main challenges, namely business legality, business strategy, and digital marketing. This program is in collaboration with President University as an official partner of the Indonesian Ministry of Manpower and consists of five stages: socialization, training, technology implementation, mentoring and evaluation, and sustainability. Through intensive training, participants are given guidance on creating a Business Identification Number (NIB) using OSS, an understanding of SWOT analysis for business strategy, and digital marketing skills using social media and e-commerce. The implementation of technology such as digital bookkeeping is also taught to improve operational efficiency. Monthly evaluations ensure the success of skill implementation, while MSME study groups are established to support sustainability. The results show that this integrated approach is able to improve the competitiveness and sustainability of MSMEs.